ICT interaction with trade, FDI and financial inclusion on inclusive growth in top African nations ranked by ICT development. (May 2023) - Wang, Wencheng; Ning, Zinan; Shu, Yang; Riti, Miriam-Kamah J.; Riti, Joshua Sunday
Abstract: The significance of ICT (information and communication technology) framework in efforts to attract foreign investment (FDI), sustain commerce, and boost financial inclusion for enhanced inclusive growth has revolutionized the global system recently. Furthermore, earlier researches on the connection between ICT and growth concentrated more on general expansion than on the kind of growth that is evenly distributed and has broader societal implications than merely growing the size of the overall economic pie. This study critically analyzes the connection between ICT diffusion and inclusive growth, considering the interactive impacts of trade openness, FDI, and financial inclusion on inclusive growth in top African nations ranked in terms of ICT development, so as to close the existing literature gap. An improved-GMM (generalized method of moments) technique, founded on panel data-set spanning the years 2000–2020, is used in the study. By employing PCA (principal component analysis) to measure inclusive growth, ICT diffusion, and financial inclusion indices, the study contributes to the body of prior research. The model also accounts for the heterogeneous impact of the interactive term between ICT diffusions and trade openness, FDI, and financial inclusion on inclusive growth. Overall, results indicate that while ICT diffusion, trade openness, FDI, and financial inclusion significantly and positively enhance inclusive growth at both the individual and interaction levels, inflation hinders it. The study suggests that policymakers should establish measures to advance ICT development, encourage trade openness, attract foreign direct investment, and improve financial inclusion because these measures have tendencies to support inclusive growth by opening up a number of opportunities. Highlights: ICT interaction with trade, FDI and financial inclusion on inclusive growth examined. PCA is used to measure inclusive growth, ICT and financial inclusion. An improved GMM technique is used to estimate the coefficients. ICT, trade, FDI and financial inclusion positively and significantly enhance inclusive growth. Advancement in ICT, encouragement of trade, attraction of FDI and improvement in financial inclusion.